Development and Consideration of 3D Transient Electromagnetic Forward Modelling for the Hydraulic Fracturing Monitoring - Huang, Xin; Yan, Liangjun; Cao, Xiaoyue; Zhou, Lei; Xie, Xingbing (Frontiers in Energy Research, 2022)
Hydraulic fracturing monitoring is an essential technical means for unconventional oil and gas development. Hydraulic fracturing monitoring can be applied to evaluate the degree of development and scale of fractures in target reservoirs and to diagnose the extent of fracturing fluid. It can then be used to estimate the stimulated reservoir volume (SRV). Therefore, it is critical to forecast reservoir yields and unconventional oil and gas resource utilization. Conventional hydraulic fracturing monitoring is predominantly based on microseismic monitoring, which can effectively delineate the range and main direction of the fracturing fractures. However, microseismic fractures is difficult to guarantee that the volume of fracturing in the seismically active fractures is equal to that in the fracturing reservoirs. Recently, the transient electromagnetic (TEM) based on the substantial conductivity difference between the fracturing fluid and the background earth has been used as an emerging technology in the field of fracturing monitoring. It can then be used to evaluate the degree of fracturing development quantitatively. Based on the background of using TEM in Hydraulic fracturing monitoring, this paper gives a short review of 3D forward TEM modelling developments and its applications for hydraulic fracturing monitoring. And the challenges of 3D forward modelling for hydraulic fracturing monitoring application have been discussed. We found that current TEM forward modeling algorithm should meet the challenges of considering fracturing medium, anisotropy and using a multi-scale forward method. Solving these technical difficulties will promote hydraulic fracturing monitoring technology for unconventional oil and gas exploration.